2023
DOI: 10.3390/su15031912
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Impact Analysis for Road Embankment Construction: Comparison of Lignin and Lime Soil Stabilization Treatments

Abstract: The last decade has witnessed increased attention toward products, services, and works with reduced environmental impacts. In the field of road construction, the use of alternative materials, wastes, or by-products obtained from industries is attracting considerable interest. The Life Cycle Assessment (LCA) is a powerful project-level tool that allows the assessment of the environmental impacts of a road infrastructure, from raw materials production to end of life phase. In this study, the environmental impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…However, the durability of stabilization techniques depends on the specific materials and processes used and the application. It is essential to conduct a comprehensive life cycle assessment (LCA) to evaluate the environmental impacts from cradle to grave, e.g., extraction of raw materials, manufacturing, transportation, construction, use, and disposal [8]. LCA provides a holistic perspective on sustainability by analyzing trade-offs between improved soil properties and potential consequences such as carbon emissions or toxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, the durability of stabilization techniques depends on the specific materials and processes used and the application. It is essential to conduct a comprehensive life cycle assessment (LCA) to evaluate the environmental impacts from cradle to grave, e.g., extraction of raw materials, manufacturing, transportation, construction, use, and disposal [8]. LCA provides a holistic perspective on sustainability by analyzing trade-offs between improved soil properties and potential consequences such as carbon emissions or toxicity [9].…”
Section: Introductionmentioning
confidence: 99%
“…This level of homogeneity is unnecessary for asphalt mixtures. The rationale behind this is that the price of bioadditives is likely to decrease by up to 40% when they are produced exclusively for the purpose of asphalt mixtures [87,101]. Furthermore, the examination and comparison of the quantity of CO 2 generated during biocompound production and the manufacturing procedures of cement and lime are conducted considering the severe environmental risks associated with the release of carbon dioxide.…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…Previous studies have reported that average kg CO 2 -eq emissions generated from the production of lignin and other biomass additive compounds produce 0.29-0.36 kg CO 2 -eq/kg of CO 2 . In contrast, lime, cement, and asphalt binder manufacturers have been estimated to generate CO 2 emissions of up to 0.94-0.99 kg CO 2 -eq/kg [35,101]. Additionally, bioadditive recycling enables the commencement of production processes immediately following their depletion, thereby potentially reducing the need for conventional additives by as much as 20% [16,102].…”
Section: Life Cycle Assessment (Lca)mentioning
confidence: 99%
“…An example of an alternative option is calcium sulfoaluminate (CSA) cement, a non-traditional stabilizer that possesses environmentally beneficial characteristics while also retaining effective soil stabilization capabilities [5][6][7][8][9]. Also, byproduct stabilizers, such as rice husk ash and lignin, are considered cost-effective and environmentally friendly substitutes for traditional and non-traditional stabilizers in various civil engineering applications [10][11][12][13]. In a recent study, the life cycle assessment (LCA) tool was employed to evaluate the environmental impact of lignin and lime.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the life cycle assessment (LCA) tool was employed to evaluate the environmental impact of lignin and lime. This assessment revealed that lignin has a significantly lower contribution to global warming potential (GWP) than lime [11].…”
Section: Introductionmentioning
confidence: 99%